Open Data in Smart Region - Kodym, O.; Unucka, J.; Létavková, D. (EAI Endorsed Transactions on Smart Cities, 2017)
Putting together up to date particular technical and organizing solutions brings us significant spin-off effecting. With support of information and communication technologies we are able to accelerate innovations, new services in region and its municipalities. We can improve life of citizens, improve regional transportation and deliver unprecedented value in many other areas. Industry 4.0 is not the goal but the means. Topics and issues in field of public transportation are discussed and some examples of open data processing are presented.